Wizer.me – organizational tool for interaction in the education system - Мусахан, Рыскүл; Боранкулова, Дина (Pedagogy and Psychology, 2021)
The article considers a program that will help teachers in the process of traditional and distance learning based on didactic ideas, quality education and innovative thinking. In the field of education, it is important not only to provide ready-made materials and valuable resources, but also to present them in visual aids so that the student can quickly understand them. The fundamental issues in the development of new curricula are the strengthening of practice-oriented work through the implementation of a systematic activity approach, the development of functional literacy of students, the systematization of the content of the discipline by redistributing educational material by education levels and strengthening interdisciplinary integration. In the proposed article, in the traditional and remote geographical educational process, the section "Physical Geography" is used for the purpose of mastering and repeating in Wizer.me the ways of using the digital platform and the ways of building a system of tasks are given. The effectiveness of work on the assessment and reflection of the sequence of tasks proposed to students, feedback is revealed. The main feature of this platform is an accessible, user-friendly, multicomponent sequence of tasks that includes functions at all stages of the lesson (brainstorming, in order to consolidate the topic, summing up and feedback).